1987
DOI: 10.1002/ajim.4700110509
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects and dust exposures in hog confinement farming

Abstract: Fifty-three hog confinement farmers and 43 control farmers were studied. Pulmonary function, total and respirable personal dust levels, and responses to a health status questionnaire were obtained for all farmers. The hog farmers' total and respirable personal dust exposures were significantly higher than the respective levels of the control farmers. Higher dust levels were associated with the use of floor (scatter) feeding, indoor feed grinding, and the use of high moisture corn feed. Pork producers reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 18 publications
3
55
0
Order By: Relevance
“…The mean MEF, FEF 5o ' and FEF 25 were slightly lower than the reference values but without significant differences between the three studied groups even when smoking habits were taken into account. Lung function values were also slightly lower for the reference farmers than for the pig farmers in the study of Holness et al (10). Lower lung function values were also found by Dalphin et al (3) among French dairy farmers.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The mean MEF, FEF 5o ' and FEF 25 were slightly lower than the reference values but without significant differences between the three studied groups even when smoking habits were taken into account. Lung function values were also slightly lower for the reference farmers than for the pig farmers in the study of Holness et al (10). Lower lung function values were also found by Dalphin et al (3) among French dairy farmers.…”
Section: Discussionsupporting
confidence: 49%
“…Each dose contained 40 ug of methacholine, and the spirometric variations were recorded 2 or 3 min after cumulative doses of 80, 240, and 560 ug of methacholine. The challenge was not performed if the subject had an observed FEVlo:predieted FEV ratio of less than 70%, and it was 10 stopped after a decrease of 20% of the FEV 10' For the analysis of the methacholine challenge, we compared the prevalence of the subjects with a fall in FEV LO that was greater than 10, 15, and 20%. They were considered responders.…”
Section: Methacholine Challengementioning
confidence: 99%
“…In contrast to the many studies of occupational exposures of swine confinement-house workers (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), only a few field studies have investigated the health effects of lower level environmental exposures. In a study of residents near hog facilities in North Carolina, Schiffman et al (26) reported that persons exposed to odors from intensive hog operations experienced "more tension, more depression, more anger, more fatigue, and more confusion" than a group of unexposed persons.…”
mentioning
confidence: 99%
“…Airborne emissions from confinement houses, cesspools, and spray fields contain ammonia, hydrogen sulfide, hundreds ofvolatile organic compounds, dusts, and endotoxins. These mixtures, which cause respiratory dysfunction in hog confinement-house workers (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and possibly lower level symptoms in nearby residents (29,30) …”
mentioning
confidence: 99%
“…Airborne emissions from confinement houses, cesspools, and spray fields contain ammonia, hydrogen sulfide, hundreds ofvolatile organic compounds, dusts, and endotoxins. These mixtures, which cause respiratory dysfunction in hog confinement-house workers (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and possibly lower level symptoms in nearby residents (29,30), are highly obnoxious odorants that affect quality of life (29)(30)(31) and may be associated with mood disorders and lowered immune function (32,3a (40). As in the case of other environmental justice problems, the presence of this polluting industry is a threat to public health because it may lower land values and quality of life and impede healthier economic developments that are needed in communities which suffer from low wages, lack of access to medical care, and poor nutritional options.…”
mentioning
confidence: 99%